STRATEGI PENGEMBANGAN AGRIBISNIS KELAPA DALAM (Cocos nucifera L.) SEBAGAI KOMODITAS UNGGULAN DI KABUPATEN BUTON UTARA - Hasrin Hasrin; Mais Ilsan; Nuraeni Nuraeni (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2023)
This study aims to analyze the coconut commodity as a leading commodity in North Buton Regency and to analyze the income of coconut farming in North Buton Regency. This research was conducted in North Buton Regency for three months, from July to October 2020. The type of data used is quantitative data derived from primary data and secondary data. Data collection is done by way of interviews, observation, and documentation. The sample in this study consisted of 60 coconut farmers and 10 informants who were determined purposively (purposive sampling). Data analysis used is qualitative descriptive analysis, LQ analysis and income analysis. The results of the study show that coconut in North Buton Regency is a superior commodity because based on the production approach the average LQ value for five years (2014-2019) is greater than one (> 1) which is 3.057. The deep coconut agribusiness subsystem in North Buton Regency includes; 1) sub-systems of production facilities such as coconut seeds, coconut peelers, fruit pulp tools, machetes, tarpaulins, sprayers, and lawn mowers; 2) farming subsystem includes planting techniques, land clearing, and harvesting; 3) processing subsystem includes production of copra and coconut shell charcoal; 4) marketing subsystem and 5) supporting advice subsystem. The average income of deep coconut farming in North Buton Regency is Rp. 16,479,910.02. The priority programs for the development of deep coconut agribusiness strategies in North Buton Regency are: 1) Improving the quality of human resources for farmers with a QSPM value of 12.38. 2) Maximizing coconut derivative products with a QSPM value of 12.01. 3) Managing deep coconut agribusiness by utilizing appropriate technology with a QSPM value of 11.96 4) Using superior variety seeds with a QSPM value of 11.86